Graphics display capabilities in web browsers - Sołtysiuk, Damian; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2021)
The article discusses the issue of displaying graphics in web browsers. A couple of methods related to its display can be distinguished. The methods discussed are: SVG, HTML5 Canvas and the WebGl graphics engine. The research was done using a dedicated web application written in Angular and TypeScript language along with the help of Two.js library for displaying 2D graphics. After analyzing all the results it concluded that, guided by the rendering time of the elements, HTML5 Canvas turned out to be the best method. On the other hand, the best method which achieves the highest number of FPS for animation is WebGl.